A Model for Padi-Based Integrated Village Development in Malaysia - Dagoy, Salvador (1989)
This study was conducted primarily to formulate a model for padi-based Integrated Village Development (TVD) in Malaysia by assessing the institutionalization, performance and elements that enhance or limit success of Asam Jawa and Mulong-Lating Integrated Development Projects. Institutionalization means the procedures, processes and participants' acceptance of the project. Qualitative and quantitative data were gathered through informant technique, interview schedule, observation methods and review of relevant documents. Two hundred resfXX1dents, 59 informants, and 23 project planners and implementers were interviewed. Respondents were selected for structured interviews by random sampling.